La regularización del trading como actividad económica y su incidencia en el sistema tributario ecuatoriano - Ochoa Castillo, Mesías Andrés (2024)
ABSTRACT: The main objective of this research was to focus on the Constitution of the Republic that recognizes the right to develop lawful economic activities and the regulation of the tax system to collect taxes through income and contributions for the activity carried out. Ecuadorian legislation is not at the forefront of new technologies, failing to legislate them completely, a situation that leads to the lack of regulation of trading as an economic activity in the country, which is not illegal, but there is no express rule that regulates the rights and obligations arising from trading. Therefore, the main objective of this research is to analyze the legal and doctrinal configuration and regulation of trading as an economic activity to determine its impact on the Ecuadorian tax system. The unit of analysis is located on the people who carry out this activity in Ecuador, where trading was studied as an economic activity, the researcher assumed a qualitative approach, a non-experimental design, applying the inductive, analytical, and descriptive methods, the research is documentary, bibliographic, analytical and descriptive. The results of the research show that the regulation of trading is relevant due to the significant progress of the standardization of digital investment since trading is not considered a non-illicit economic activity within the Ecuadorian state, which would lead to the opening of multiple tax crimes such as tax evasion and even organized crime such as money laundering, since the lack of rules, regulations or any reform to strengthen the digital economy that includes digital assets, would cause them to remain stagnant without the possibility of due process.